Cyclosporin A in idiopathic chronic fibrosing interstitial pneumonia without idiopathic pulmonary fibrosis - Takei, Reoto; Arita, Machiko; Tokioka, Fumiaki; Tachibana, Hiromasa; Tokumasu, Hironobu; Ishida, Tadashi (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: We have sometimes observed interstitial pneumonia which had chronic course and unknown causes but not diagnosed as idiopathic pulmonary fibrosis (IPF). However, the treatment strategy was not established definitely. To clarify the usefulness of cyclosporin A (CsA) in idiopathic chronic fibrosing interstitial pneumonia (iCFIP) without IPF, we examined longitudinal changes in pulmonary physiology. Methods: Japanese patients with iCFIP without IPF treated with CsA were identified retrospectively. Linear mixed-effects models were used to evaluate changes in pulmonary physiology after adjusting for age, sex, and smoking history. Primary outcomes were longitudinal trajectories of the percent predicted forced vital capacity (%FVC), percent predicted diffusing capacity for carbon monoxide (%DLco), and composite physiologic index (CPI) before and after CsA. Results: Thirty-three patients were included. Before CsA initiation, %FVC, %DLco, and CPI declined at rates of 9.1%, 8.6% and −7.1 per 1 year, respectively. After CsA initiation, the gradient of %FVC showed significant improvements in 0–1 years (6.2%±3.0%; P